Positive response to niraparib in chemo-refractory patients with metastatic appendiceal mucinous adenocarcinoma harboring ATM mutations: A case report - Wang, Junhui; He, Huijuan; Xu, Wansu; Chen, Jianxin (Frontiers in Oncology, 2023)
Background: Appendiceal mucinous adenocarcinoma, one kind of specific colorectal cancer types, is lowly prevalent and rarely diagnosed in clinical practice. In addition, there has been limited standard treatment strategies established for patients with appendiceal mucinous adenocarcinoma, especially with metastatic disease. The regimens for colorectal cancer, which adopted in appendiceal mucinous adenocarcinoma, usually resulted in limited effectiveness. Case presentation: Herein, we presented a case of chemo-refractory patient with metastatic appendiceal mucinous adenocarcinoma harboring ATM pathological mutation of exon 60, c.8734del, p.R2912Efs*26, has achieved persistent response to salvage treatment of niraparib, with disease control time reached 17 months, and still in extension. Conclusions: We supposed that appendiceal mucinous adenocarcinoma patients harboring ATM pathological mutations may respond to the treatment of niraparib, even without HRD status, however, need further confirmation in a larger cohort.